Digital Physiotherapy Intervention in Health Care Delivery– A Narrative Review - Rajkumar Krishnan, Vasanthi; Yughdtheswari, Muniandy; Kaanmalar, Asoghan (INTI International University, 2019)
Background and Objective: Delivering health care with information and communication technology has become an innovative form to address various health needs. Poor demand for services, adherence or follow up plans, inaccessibility of facilities, and high cost of treatment are the major challenges faced by the health care system that need to be overcome. So the objective of this narrative review is to explore how digital physiotherapy intervention is supportive and improve the quality of healthcare in the current clinical setup. Methods and Results: Electronic papers up to May 2019 were searched in Medline/PubMed rigorously. Total of 10 potential relevant titles was identified and reviewed. We summarized these studies emphasizing how digital intervention could support or enhance the current rehabilitation or physiotherapy practice. Conclusion: Digital intervention is believed to have an impact on the client’s performance, self-management and adherence of exercise program at the home in the absence of health care providers to a certain extent. The digital intervention act as the driver or facilitator in improving the client’s health status.